EVALUASI DESAIN DRAINASE RUNWAY STRIP DI BANDAR UDARA INTERNASIONAL JUWATA TARAKAN - Setyo Hariyadi; Firmanto Yusuf Aditia; Fahrur Rozi (Approach : Jurnal Teknologi Penerbangan, 2019)
Lifted from the problem of puddles on the runway strip surface of Juwata Tarakan International Airport, especially during heavy rains and resulting in overflow of drainage water which can cause damage to the runway strip surface. From this problem arises an impact that can reduce the value of safety and security of airport operational technical standards, therefore an analysis of the design of the runway strip drainage at Juwata Tarakan International Airport is made. The analysis was conducted with the aim of knowing the suitability of the existing dimensions of the runway strip with the existing hydrological analysis. With the 10 yearly rainfall data in the analysis, the results show the existence of conditions (fulfilling or not) Furthermore, after knowing the results of the analysis of the existing design which states the existence of the problem, a new dimension is planned with reference to the hydrological and hydraulic analysis. From the re-design calculation, it is obtained the runway strip drainage dimension with a flow rate of 1.77 m3 / sec and the calculation of its dimensions in the form of a trapezoid with drain depth (d) = 1.1 meters; bottom width (b) = 1 m; peak width (T) = 2 meters; freeboard (W) = 0.5 meter; and drainage slope (z) = 0.5 meter.